Information sharing behavior in mobile message / Farihah Mokhtaruddin - Mokhtaruddin, Farihah (2016)
Mobile instant messaging is being used by people in the world to communicate and sharing information or knowledge. The popular application had been used by user is Whats App. The information are not limit to the text only compare to Short Message Service (SMS), they also can share image, audio, video, contact and location. The information can be shared easily and could make the youth over-used it and wasting their time with nonsense gossiping, viral and chatting. Other than that, some youth use WhatsApp to share untrue story or make viral of the humiliating video as it's an easy medium to share stuff like those. This project identify factors that lead youth using WhatsApp as a medium to share information with their friends and examine the behavior of youth towards using WhatsApp in sharing information. In order to complete this study, quantitative approach will be used and the questionnaires will be as the instruments to gather the data from the respondents. Since, the scope are people around the age of youth's age, secondary school students will become the respondents of this research. The finding revealed the factors of influencing youth share information using Whats App is easy to use which means that WhatsApp application is not too complicated to use since it reduces the users time to log in and log out by giving them access whenever internet is available in just a click in WhatsApp icon. From the understanding, the factors and behavior from sharing information using WhatsApp will give advantages to youth. Since WhatsApp is easy to use, the youth easy to forward to others when receiving the information instead of not forwarding to others when receiving the information. However, not all type of information that they shared. Study show that information that most to share is study related matters.